Impant Failure Post ORIF Femur - Muhammad Bayu Rizaldy; Alya Athaya (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
A femur fracture is a break or loss of continuity of femur, clinically this condition can present as an open or closed femur fracture. Adequate management of fractures is important to prevent short-term and long-term complications. Management of femur fractures can be performed through open or closed reduction. Open reduction is achieved through surgical intervention, with bone fragments reduced using internal fixation (ORIF).ORIF failure can happen due to several factors, such as poor bone quality, biomechanical failure of the fixation device, infection, and poor rehabilitation. This failure can lead to nonunion, implant loosening, and even other serious complications. A 20-year-old male patient came with complaints of persistent pain in his left leg after vehicle accident four months ago. ORIF was performed on the patient four months ago, and the patient had improved. After the procedure, the patient accidentally put his weight on the wrong side while walking and fell, causing the left leg become painful again. Physical examination showed deformity, tenderness, and limited range of motion, with good sensation, detectable dorsalis pedis artery pulsation, and CRT < 2 seconds. X-ray of the left femur revealed a left femur fracture fixed with a plate and screws. The patient was subjected to surgical intervention specifically Re-ORIF and provided with antibiotics and analgesics. The patient also provided with education post-operative care and how to properly rehabilitation to prevent re-failure.